(untitled) (International journal of medical sciences, 2026)
Latin has historically served as the foundation of medical terminology and continues to function as a universal linguistic system in international medical communication. Despite no longer being a spoken language, Latin remains essential in anatomy, clinical terminology, pharmacology, and biological nomenclature. This article examines the historical development of Latin in medicine, its structural and linguistic advantages, and its role in ensuring precision, universality, and terminological standardization in global healthcare practice. Special attention is given to the integration of Latin terminology into modern medical education and professional communication. The study demonstrates that Latin remains a crucial element of medical discourse, contributing to clarity, scientific continuity, and intercultural understanding in contemporary medicine.